The Role Of Organizational Culture In Career Development For Improving Employee Performance At Perumda Tirta Pakuan Bogor - Teguh Setiadi; Mardi Siswoyo; Fernandez Hutagalung; Sri Sundari; Marisi Pakpahan (International Forum of Researchers and Lecturers, 2024)
The success of Perumda Tirta Pakuan Bogor is greatly influenced by the performance of its employees. Good work results can help Perumda Tirta Pakuan Bogor in achieving the goals and objectives that have been set. In other words, the better the employee's performance, the easier it will be to achieve the goals of Perumda Tirta Pakuan Bogor. On the other hand, if employee performance is low, it is not easy for Perumda Tirta Pakuan Bogor to achieve its goals. So the role of employee performance is a factor that cannot be separated from the objectives of Perumda Tirta Pakuan Bogor so that the quality of employee performance will influence the achievement of the objectives of Perumda Tirta Pakuan Bogor. This research aims to determine and analyze the role of organizational culture and career development in improving the performance of Perumda Tirta Pakuan employees in Bogor City. This research uses descriptive qualitative, with the data collected mostly in the form of words or images rather than numbers. The objects of this research are employees at Perumda Tirta Pakuan, Bogor. The research carries out analysis of the data obtained through interviews and other documents by combining and selecting data that is close to suitability related to the research study. The research results show that the role of organizational culture in improving employee performance at Perumda Tirta Pakuan Bogor is based on a talent management strategy which is an integrated system, designed to improve performance through the process of attracting and selecting, developing, utilizing and retaining employees who have skills and talents. in order to meet current and future organizational needs. The role of career development in improving the performance of Perumda Tirta Pakuan employees in Bogor is known that career development is an activity for future career planning by the employees themselves or the company concerned so that the company can also develop itself optimally.